Dual-regulatory miRNAs: master regulators and therapeutic targets in bone-metastatic breast cancer - Meng, Feifei; Zhang, Mengdi; Pu, Dongqing; Shi, Guangxi; Li, Jingwei (Frontiers in Molecular Biosciences, 2025)
Breast cancer bone metastasis involves dynamic reprogramming of transcriptional networks and cellular homeostasis. Current primary treatment strategy relies on palliative care, and the search for effective therapeutic targets remains a critical challenge. MicroRNAs (miRNAs), endogenous non-coding RNA molecules, exert precise regulation of gene expression through sequence-specific binding to the 3′ UTR of target mRNAs. Accumulating evidence has established miRNAs as pivotal regulators of breast cancer and its metastatic bone disease. Depending on their target genes, individual miRNAs may function as oncogenic miRNAs (oncomiRs) or as tumor suppressor miRNAs (tsmiRs), and hold potential as biomarkers for diagnosis and prognosis. This review systematically analyzes the regulatory mechanisms of critical miRNAs and their target genes in breast cancer bone metastasis, offering novel insights for early diagnosis and targeted therapeutic strategies.